IMPLEMENTASI MANAJEMEN SEKURITI TERHADAP SEBUAH KONFLIK PADA LEMBAGA PEMASYARAKATAN - Tubagus Hedi Saepudin; Ryuken, Raihan Nuraditya Pratama, Muhammad Miftahul Huda, Gilang Adel Kuswara, Muhammad Teguh Andria (Adisam Publisher, 2024)
One important step in facing and resolving conflict in an organization is implementing security management. Differences in opinion, interests and goals are a number of factors that cause conflict. In recent years, conflict has become the most common problem faced by organizations, both in business and education. In this article, we will discuss the application of security management to conflict and how security management can help resolve conflict and improve employee performance. We will also discuss several examples of how security management has been implemented in the literature study chosen as the method used in writing this journal. Reading, taking notes, and managing research materials are part of a series of actions known as literature studies in some organizations. This study found that the application of security management to conflicts in correctional institutions in Indonesia allows the use of preventive and repressive approaches simultaneously to achieve optimal security. Preventive approaches include visitation, inmate placement, remission, and treatment. By improving prisoners' psychological conditions and providing them with incentives, visitation and remission programs, for example, improve their morale and encourage them to behave well. This program aims to reduce the possibility of conflict.